Syngas Production from Methane Dry Reforming Over 15wt%Ni/85wt%CaFe2O4 Catalyst - Hossain, M. Anwar; Ayodele, Bamidele V.; Cheng, C. K.; Khan, Maksudur R. (Universiti Malaysia Pahang, 2016)
In the present study, syngas production from methane dry reforming over 15wt%Ni/85%CaFe2O4 catalyst was investigated. The CaFe2O4 was synthesized by sol gel method using stoichiometric ratio of Ca(NO3)2.4H2O and Fe(NO3)3.9H2O mixed in 30% aqueous NH3 solution. The 15wt%Ni/85%CaFe2O4 catalysts was synthesized by impregnating required amount of aqueous solution of Ni(NO3)2.6H2O in 1g of CaFe2O4. The as-synthesized catalyst was characterized by XRD, SEM, EDX and FTIR for phase identification and crystallinity, morphology, elemental composition, and nature of chemical bonds. The catalytic activity of the catalyst was tested in methane dry reforming using a fixed bed continuous flow reactor. The catalyst activities were measured in terms of the reactant (CH4 and CO2) conversions and the products (H2 and CO) yield. The activity of catalyst in the methane dry reforming reaction resulted to highest CH4 and CO2 conversions of 90.4% and 87.6% respectively with a corresponding H2 and CO yield of 73.42% and 74.43% respectively. Syngas with H2:CO ratio of 0.986 was obtained from the methane dry reforming reaction over the 15%Ni/CaFe2O4 catalyst making it suitable for use as chemical intermediate for the synthesis of oxygenated fuels.